2020
DOI: 10.1063/5.0014179
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dynamics origin of high photocatalytic activity of mixed-phase anatase/rutile TiO2

Abstract: Mixed anatase/rutile TiO2 exhibits high photocatalytic activity; however, the mechanism underlying the high performance of the mixed phases is not fully understood. We have performed time-domain ab initio calculations to study the exited state dynamics in mixed phase TiO2 and to investigate the impact of an oxygen vacancy on the dynamics. The anatase(100)/rutile(001) heterostructures with and without an oxygen vacancy used in this work exhibit type II band alignment with the conduction band of rutile residing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 76 publications
0
27
0
Order By: Relevance
“…Our previous simulations using trajectories of similar length showed good results for a broad range of materials, including pristine and doped TiO 2 and TiO 2 sensitized with other semiconductors. 62 , 71 , 96 , 97 …”
Section: Results and Discussionmentioning
confidence: 99%
“…Our previous simulations using trajectories of similar length showed good results for a broad range of materials, including pristine and doped TiO 2 and TiO 2 sensitized with other semiconductors. 62 , 71 , 96 , 97 …”
Section: Results and Discussionmentioning
confidence: 99%
“…Recently, several theoretical [45] and experimental studies [42][43][44][45] showed that mixed phases (rutile/anatase) [50] and (anatase/brookite) [51] exhibit higher photocatalytic activity than pure anatase or rutile phase due to the interface rutile/anatase heterojunction which reduces the electron (e -)-hole(h + ) recombination [52]. Y. Wei [53] proved using ab initio calculation that the lifetime of charges separation (e -, h + ) in TiO2 mixed phase is longer than in pure rutile and anatase phases. It was also found that a ternary mixture of anatase, rutile and brookite phase inhibits the recombination of charges pairs by capturing the electrons [54][55].…”
Section: Introductionmentioning
confidence: 99%
“…38−40 The current NA-MD approach treats light and fast electrons quantum mechanically while describing the heavy and slow nuclei (semi)classically. This approach has been successfully applied to study photoexcitation charge dynamics in a broad range of systems, including metal oxides, 41 BP, 42 and other two-dimensional materials, 43 as well as metal halide perovskites. 44 The electronic structure calculations and AIMD were performed using Vienna ab initio Simulation Package (VASP).…”
mentioning
confidence: 99%
“…The decoherence-induced surface hopping (DISH) algorithm and the classical path approximation were employed, , as implemented in the time-dependent Kohn–Sham DFT (TD-DFT). Phase correction was applied to correct the arbitrary phase in the adiabatic wave functions, and the NAC was computed with the projector-augmented wave (PAW) potentials. The current NA-MD approach treats light and fast electrons quantum mechanically while describing the heavy and slow nuclei (semi)­classically. This approach has been successfully applied to study photoexcitation charge dynamics in a broad range of systems, including metal oxides, BP, and other two-dimensional materials, as well as metal halide perovskites …”
mentioning
confidence: 99%